The best performance method to Solve WSD Problem: Comparative Study - F Zopon AL_Bayaty, Boshra; Joshi, Shashank (International Journal of Computer Sciences and Engineering, 2014)
Word is used to convey or extract meaning of particular information. If data that is meaning associated with word is misinterpreted then it will lead to incorrect data. To avoid this problem these is need to resolve meaning of given word correctly. This task can be performed with the help of repository of ambiguous word WordNet2.1 which gives meaning and POS of given word. Now with the help of some other parameter this data could be utilized. That parameter is nothing but context around given word.